The bishop’s responsibility for his presbyterate in the context of sexual offences committed by priests - Majer, Piotr (Prawo Kanoniczne, 2023)
The aim of this paper is to answer the question: How should the bishop act towards his presbyterate so that its members would not commit sexual offences, particularly the most serious ones? The following issues are presented: the relationship between a bishop and his presbyterate, the bishop’s responsibility for the admission of proper candidates to ordination, the assignment of offices and functions in the diocese, the bishop’s obligation to watch over the discipline of the clergy, the bishop’s responsibility for granting the faculty of hearing the confessions.